DEFINITION csubc_refl()
TYPE =
∀g:G.∀c:C.(csubc g c c)
BODY =
assume g: G
assume c: C
we proceed by induction on c to prove csubc g c c
case CSort : n:nat ⇒
the thesis becomes csubc g (CSort n) (CSort n)
by (csubc_sort . .)
csubc g (CSort n) (CSort n)
case CHead : c0:C k:K t:T ⇒
the thesis becomes csubc g (CHead c0 k t) (CHead c0 k t)
(H) by induction hypothesis we know csubc g c0 c0
by (csubc_head . . . H . .)
csubc g (CHead c0 k t) (CHead c0 k t)
we proved csubc g c c
we proved ∀g:G.∀c:C.(csubc g c c)